Combined hazard assessment of mycotoxins and their modified forms applying relative potency factors: Zearalenone and T2/HT2 toxin. (September 2019) - Steinkellner, Hans; Binaglia, Marco; Dall'Asta, Chiara; Gutleb, Arno C.; Metzler, Manfred; Oswald, Isabelle P.; Parent-Massin, Dominique; Alexander, Jan
Abstract: This paper describes a methodology for hazard assessment of groups of related substances for which toxicity data are insufficient, and which utilises, next to conventional toxicological assessments and mechanistic information, the derivation of relative toxicity potency factors (RPFs). Zearalenone (ZEN) and T-2 toxin (T2) and HT-2 toxin (HT2) and their modified forms have been used as examples. A tolerable daily intake (TDI) for ZEN of 0.25 μg/kg bw was established. In vitro and in vivo studies suggested that modified forms of ZEN act via the same mode of action as ZEN (oestrogenicity). Results from in vivo uterotrophic assays were used to establish RPFs, allowing inclusion the different modified forms in a group TDI with ZEN. A TDI for the sum of T2/HT2 of 0.02 μg/kg bw per day and an acute reference dose (ARfD) of 0.3 μg/kg bw for the sum of T2/HT2 was established. In vitro studies show that phase I metabolites of T2/HT2 act via a similar mode of action as their parent compounds, namely protein synthesis inhibition with immune- and haematotoxicity. The phase I metabolites as well as conjugates of T2/HT2 and their phase I metabolites can be included in a group TDI with T2/HT2 applying RPFs. Highlights: Modified forms of ZEN and T2/HT2 have been described and their to occurrence in food quantified. Toxicity of ZEN and T2/HT2 has been assessed and HBGVs were established. Potency factors relative to ZEN and T2/HT2 were established for modified forms to compensate for the lack of toxicity data. The methodology developed can be applied for other groups of structurally related substances.